Cardiac autonomic neuropathy in nonobese young adults with type 1 diabetes - Kim, Hwa Young (Ann Pediatr Endocrinol Metab, 2019)
PURPOSE: The aim of this study was to evaluate the prevalence and risk factors for cardiac autonomic neuropathy (CAN) in nonobese nonobese young type 1 diabetes mellitus (T1DM) patients without micro- or macrovascular complications. METHODS: CAN was assessed in 95 patients with T1DM, aged 18–29 years, using standard cardiovascular reflex tests – heart rate response to deep breathing, standing, and the Valsalva maneuver and blood pressure response to standing. Furthermore, power spectral analyses of overall heart rate variability (HRV), standard deviation of NN intervals (SDNN), and total power (TP) were tested with DiCAN. CAN was defined as abnormal results for at least 1 of the 4 cardiovascular reflex tests. RESULTS: The prevalence of CAN was 12.6%. The frequency of one and 2 abnormal reflex tests was 10.5% and 2.1%, respectively. No significant differences were observed in age, sex, mean hemoglobin A(1c) (HbA(1c)) level, and duration of diabetes with respect to presence of CAN. Patients with CAN exhibited lower overall HRV parameters (SDNN and TP) compared with those without CAN even though there was no statistical significance. In multivariable analyses, higher mean HbA(1c) level was significantly associated with lower overall HRV (β=-44.42, P=0.002 for SDNN and β=-2.82, P<0.001 for TP). CONCLUSIONS: CAN can be detected in 12.6% of young adult T1DM patients even without other micro- or macrovascular complications. Glycemic control is the main determinant to maintain overall HRV and prevent CAN.